Native Valve Infective Endocarditis with Osteomyelitis and Brain Abscess Caused by Granulicatella adiacens with Literature Review. (30th July 2019) - Patil, Sachin M.; Arora, Niraj; Nilsson, Peter; Yasar, S. J.; Dandachi, Dima; Salzer, W. L.
Abstract : Granulicatella adiacens is a type of NVS (nutritionally variant streptococci) rarely causing infective endocarditis (IE). NVS are fastidious and unable to sustain growth on routine culture media due to lack of specific nutrients. Endocarditis caused by NVS due to their virulence is associated with higher treatment failures and mortality rates. New antimicrobial susceptibility patterns are indicative of a significant rise in penicillin resistance and susceptibility differences between NVS subspecies. Initial empirical therapy is essential as a delay in using the appropriate agent leads to poor results. We present a case of an immunocompetent young female with recent intravenous drug abuse resulting in native mitral valve endocarditis with ruptured chordae tendineae and septic embolization, causing brain abscess and lumbar spine osteomyelitis. She was transferred to a tertiary center where she underwent mitral valve replacement successfully and treated with six weeks of intravenous vancomycin and ertapenem. To our knowledge, ours is the first case report of G. adiacens endocarditis in an adult with brain abscess and osteomyelitis with an excellent response to antibiotic therapy. Based on our case report, literature review, and new antimicrobial susceptibility patterns, updates to treatment guidelines are suggested to improve the therapeutic outcomes.